2019
DOI: 10.1002/ange.201814143
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Reaction of Silacyclobutanes with Unactivated Alkynes to Afford Silacyclohexenes

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…Recently, silacyclobutanes (SCB) have attracted much attention, because the highly strained ring bond can activate the silicon‐carbon reaction with many transition‐metals (Pd, Ni, Rh, Co, Ag, Pt) to deliver ring expansion and ring opening products [27–34] . During the study of platinum‐catalyzed ring‐opening polymerization of SCB, Kawakami and co‐workers reported the only example of cross‐redistribution between SCB and Et 3 SiH, but neither substrate scope nor mechanism study was reported [34] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, silacyclobutanes (SCB) have attracted much attention, because the highly strained ring bond can activate the silicon‐carbon reaction with many transition‐metals (Pd, Ni, Rh, Co, Ag, Pt) to deliver ring expansion and ring opening products [27–34] . During the study of platinum‐catalyzed ring‐opening polymerization of SCB, Kawakami and co‐workers reported the only example of cross‐redistribution between SCB and Et 3 SiH, but neither substrate scope nor mechanism study was reported [34] .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only Shintani, Hayashi, Nozaki et al and Song have succeeded in forming six-membered tetraorgano-substituted silicon-stereogenic silanes (Fig. 1b ) 39 43 , while the construction of Si-chirality on six- and seven-membered triorgano-substituted monohydrosilanes via asymmetric catalysis is still unknown to date, which is presumably due to a lack of general and efficient synthetic methods. Given the increasing demand for the synthesis of novel functional-materials-oriented silicon-bridged biaryls, construction of six- or seven-membered monohydrosilanes in a chiral version is highly attractive.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only Shintani, Hayashi, Nozaki et al and Song have succeeded in forming six-membered tetraorgano-substituted silicon-stereogenic silanes (Fig. 1b) [36][37][38][39][40] , while the construction of Si-chirality on six-and seven-membered triorgano-substituted monohydrosilanes via asymmetric catalysis is still unknown to date, which is presumably due to a lack of general and e cient synthetic methods. Given the increasing demand for the synthesis of novel functional-materials-oriented silicon-bridged biaryls, construction of six-or seven-membered monohydrosilanes in a chiral version is highly attractive.…”
Section: Introductionmentioning
confidence: 99%